RAPD ANALYSIS TO DETECT SOMACLONAL VARIATION OF PINEAPPLE IN VITRO CULTURES DURING MICROPROPAGATION - Ika Roostika; Nurul Khumaida; Sintho Wahyuning Ardie (BIOTROPIA, 2015)
Plant off-type formation has become a concern in pineapple micropropagation, and reliable methods are required to detect and minimize this problem. This study was conducted to confirm the occurrence of somaclonal variation during the micropropagation of pineapple clone Simadu. The effects of culture period (long vs. short duration) and regeneration methods (direct organogenesis, indirect organogenesis, and somatic embryogenesis) were evaluated to determine their contribution to somaclonal variation. RAPD analysis using ten primers was performed to confirm genetic variation. The results showed that RAPD assays could be applied for early detection of somaclonal variation in pineapple, with OPA primers performing better than OPJ primers. Phenotypic variation observed in four-year-old field-grown pineapple plants and plantlets was associated with genetic variation. The findings demonstrated that the long culture period was the main factor contributing to somaclonal variation, while regeneration method and plant growth regulators also played a role in inducing genetic changes. Newly initiated cultures showed a higher level of genetic similarity. Therefore, applying an appropriate micropropagation strategy is necessary to minimize plant off-types. It is recommended to avoid using long-term cultures as mother stock and to apply direct organogenesis rather than indirect organogenesis or somatic embryogenesis for pineapple micropropagation.